2002
DOI: 10.1067/mva.2002.127966
|View full text |Cite
|
Sign up to set email alerts
|

Secondary procedures after endovascular aortic aneurysm repair

Abstract: Secondary procedures after EAR are common. Reinterventions can be grouped temporally on the basis of indication. Treatment for limb ischemia is predominately early (>/=3 months), whereas treatment for endoleaks occurs at approximately 1 year and interventions for migration predominate after 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 12 publications
2
43
1
1
Order By: Relevance
“…Again using their scoring system (0 to 3) for stratifying incremental risk, Becker et al (1141) ENDOGRAFT-RELATED COMPLICATIONS. Secondary interventions are common after endovascular aortic aneurysm repair and often are performed within months for limb ischemia, within 1 year for endoleaks, and after 2 years or more for graft migration (1207). Aneurysm rupture is a rare event in most series, possibly because of the recognized importance of serial computed tomography scanning to detect continued aneurysm expansion.…”
Section: Late Survival and Complication Ratesmentioning
confidence: 97%
“…Again using their scoring system (0 to 3) for stratifying incremental risk, Becker et al (1141) ENDOGRAFT-RELATED COMPLICATIONS. Secondary interventions are common after endovascular aortic aneurysm repair and often are performed within months for limb ischemia, within 1 year for endoleaks, and after 2 years or more for graft migration (1207). Aneurysm rupture is a rare event in most series, possibly because of the recognized importance of serial computed tomography scanning to detect continued aneurysm expansion.…”
Section: Late Survival and Complication Ratesmentioning
confidence: 97%
“…ENDOGRAFT-RELATED COMPLICATIONS. Secondary interventions are common after endovascular aortic aneurysm repair and often are performed within months for limb ischemia, within 1 year for endoleaks, and after 2 years or more for graft migration (1207). Aneurysm rupture is a rare event in most series, possibly because of the recognized importance of serial computed tomography scanning to detect continued aneurysm expansion.…”
Section: Late Survival and Complication Ratesmentioning
confidence: 99%
“…[3][4][5] One of the main reasons for additional surgery is graft limb occlusion. Conners et al 6 describe the postimplantation complications of a variety of graft devices. This series showed that 19.6% of the patients undergoing EVAR required further intervention, the majority of which tend to occur in the fi rst 90 days, and 7.3% of these were due to graft limb occlusion.…”
Section: Discussionmentioning
confidence: 99%